Stimulation of Phagocytic Activity of Human Polymorphonuclear Leukocytes in Vitro Using 10 mW He-Ne Laser. - Anwer, Ayad G. (Iraqi Journal of Laser, 2005)
Stimulative effect of 10 mW He-Ne laser on the phagocytic activity of human polymorphonuclear leukocytes( PMNs) has been studied in vitro. Normal polymorphonuclear leucocytes were isolated from the human peripheral blood. A mixture of 0.25 ml of Hanks solution, 0.25 ml of serum, 0.25 ml of Candida albicans suspension and 0.25 ml of PMNs suspension was prepared. The samples of mixture of PMNs and Candida were subdivided in 1 ml ependrof tubes and irradiated to He-Ne laser for 1, 3, 5, 10 and 20 min. The diameter of the irradiated area was 0.8 cm. For calculation of Phagocytic index before and after irradiation, the samples were incubated (37°C) at 5, 15, 30, 60 min. The slides of samples were prepared and stained using Giemsa stain. The results showed that the bio-stimulative effect of 10 mW He-Ne laser on the phagocytic activity of( PMNs) is more observable at 3 min exposure time with 5 mW/cm2 power density. Many action mechanisms were reviewed and discussed in the term of possible photo- acceptor when cells are irradiated to laser.